ALCEA: The Architecture Life-Cycle Effect Analysis Method - Axelsson, Jakob; Bilic, Damir; Brahneborg, Daniel; Froberg, Joakim; Gustavsson, Henrik; Jongeling, Robbert; Sundmark, Daniel (IEEE Open Journal of Systems Engineering, 2024)
This article describes the architecture life cycle effect analysis (ALCEA) method, a structured method for evaluating proposed new architectures for software-intensive systems. The method evaluates a proposed architecture by quantifying its effect on the performance of system life-cycle phases. The method is instantiated by identifying the relevant life-cycle phases of the system under investigation and a set of evaluation functions that capture, in terms of basic factors, the effect of different architectural decisions on key life-cycle PAs, such as revenue, operating resources, and investments. The method results in a transparent cost and revenue structure, documented in a tabular form, based on quantifiable factors from the developing organization. The results of the method can be used directly as part of a business case, and their robustness can be estimated by sensitivity analysis. The ALCEA method is designed for system-level architectural analysis, covering both software and hardware aspects. In this article, we introduce the ALCEA method and provide a detailed example of how to apply it in the evolution of embedded systems. Moreover, we share early experiences of using the method in large-scale industrial settings.